EFFECT OF WASTE PLASTIC AND CRUMB RUBBER ON PROPERTIES OF SEMI DENSE BITUMINOUS CONCRETE MIX - Dubey, Vaibhav; Parihar, Satish (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Plastic is used in day to day life. So, it’s a well- known thing that more waste would be generated throughplastic. It is discarded either by burning or by burying it in thesoil. Due to the non-biodegradability of the plastic it’s not easyto get rid of it through natural processes prevailing in the environment. So, one way in which plastic could be reused is by using it in pavement. An effort of using waste plastic in coating the aggregates is being engrossed in this study. Crumbrubber made from waste tires is also used in this study to modify the bitumen. Earlier studies have proven plastic and crumb rubber effective in increasing the strengths of pavements. So, taking this idea plastic coating is done in the aggregates and bitumen is modified with crumb rubber to check the results. The low-density plastic is taken in use. Temperaturevarying between 120 ˚C - 160 ˚C gives the softening point of the plastics being used. They do not produce any toxic gases during heating but they get often Edan laminate the aggregates. The study focuses on using different percentages of plastic in coating aggregates and different percentages of crumb rubber & study their behavior. The bitumen VG-30 is used as a binderin the mix. The performance tests including, Marshall Stabilitytests are to be conducted to find stability, density, optimum binder content and voids. The first phase of investigation focuses in the next study CRUMB RUBBER Modified Bitumen will be used in place of normal VG-30 bitumen.